Factors associated with repeated pregnancy in postpartum adolescent mothers under 20 years of age Ratchaburi Province - มีแก้ว สุภาภรณ์ (Hua Hin Medical Journal, 2019)
Objective : to study factors associated with repeated pregnancy in postpartum adolescent mothers under 20 years old. After birth in the center hospital, general hospital and community hospitals. In Ratchaburi 11 hospitals, 10 districts. Material and Method : descriptive research. The sample size consisted in postpartum adolescent mothers under 20 years old. After birth in the center hospital, general hospital and community hospitals. In Ratchaburi 11 hospitals, 10 districts. And welcome to the research can speak and speak thai. 166 samplesize Calculate by Infinite population proportion Wayne W., D. (1995). Descriptive statistics, analyze data with descriptive statistics include percentage, average, standard deviation, analyze the relationship between variables using chi-square statistics. And analyze the relationship between personal factors. Behavioral factors. Socio - economic factors with inference statistics chi - square test หรือ Fisher’s exact test. Results : The study was associated with repeated pregnancies in adolescent mothers under the age of 20 years. It was found that adolescents did not study have a higher chance of pregnancy than teens and found that the profession is related with repeated pregnancies in adolescent mothers under the age of 20. It was found that the occupation of the contracted employment is higher than the trade profession and unoccupation understanding in health factors to prevent unwanted pregnancy have related in repeated pregnanacy of adolescent mothers under age 20, with adolescent mothers have understanding in health factors in such a low level more than the one who have understanding in health factors in moderate and high level and the other factors were not associated.